âSPINNER PULLING OILâELABORASI PENERAPAN TEKNOLOGI PENGENTAS MINYAK OTOMATIS DALAM PENINGKATAN PRODUKTIFITAS ABON IKAN DI KOPERASI WANITA SRIKANDI, DESA BANTUREJO, KECAMATAN NGANTANG, KABUPATEN MALANG - Nugraha, Muhammad Agung (Program Kreativitas Mahasiswa - Teknologi, 2014)
Banturejo village is a village in the region Ngantang, Malang regency, East Java, province of Indonesia which has agricultural commodities, livestock and fisheries abundance, as well as close to the tourist sites, namely Selorejo Lake. Fishery commodities is the flagship of the village Banturejo and continue to develop. Besides fish produced from reservoirs, currently there are many citizens who do catfish farming. Catfish are sold directly for consumption and sale around Selorejo Lake. The existence of a superior product for souvenirs can be used as a complement to visitors for souvenirs. Women Cooperative (Kopwan) Heroine is located in the village Banturejo, Ngantang, Malang capture this business opportunity by processing the fish into shredded fish sources. Shredded fish introduced by the consideration that the processed products have a good chance to be a typical souvenirs Selorejo Lake is a high chance. Making shredded fish produced by Heroine Kopwan still using the conventional method is very simple and the result is still a lot of oil content in the floss. In addition, the production capacity of 10 kg of shredded fish is only able to meet 25% of consumer demand. "Oil Pulling Spinner" is a creative solution that is applied to overcome the problems of partners, as means to alleviate the oil in the manufacture of food products. In this case, the resulting product "Spinner Pulling Oil" can be applied in the elaboration of fishing effort through the harness spinner shredded products especially in Women Cooperative Heroine, Banturejo Village, Ngantang, Malang. Thus, expected by the "Oil Pulling Spinner" can explore fishery resources in the village Banturejo and is expected to improve the welfare of society. Spinner Tool Oil Pulling can set rotation (rpm) tool automatically and optimally to reduce the oil in a shredded. For the introduction and marketing tool widely shredded products, publications done using print, electronic and online. So shredded sold in large quantities.Keywords : Spinner Pulling Oil, shredded, Women Cooperative (KOPWAN), Banturejo Village